2016
DOI: 10.1016/j.exer.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of visual function and retinal structure following acute light exposure in the light sensitive T4R rhodopsin mutant dog

Abstract: The effect of acute exposure to various intensities of white light on visual behavior and retinal structure was evaluated in the T4R RHO dog, a naturally-occurring model of autosomal dominant retinitis pigmentosa due to a mutation in the Rhodopsin gene. A total of 14 dogs (ages: 4–5.5 months) were used in this study: 3 homozygous mutant RHOT4R/T4R, 8 heterozygous mutant RHOT4R/+, and 3 normal wild-type (WT) dogs. Following overnight dark adaptation, the left eyes were acutely exposed to bright white light with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Suppression of Mutant RHO with shRNA 820 . To verify the efficiency of shRNA 820 in heterozygous mutant retinas that express both WT and mutant RHO alleles, subretinal injections of AAV-shRNA 820 were performed over a range of titers (1 × 10 11 to 10 × 10 11 vg/mL) in 10 RHO-mutant eyes that were followed for 8-10 wk postinjection (SI Appendix, Table S1 groups D and E) Since the RHO-mutant dog retinas are highly sensitive to light (45)(46)(47)(48), the animals were housed under dim red light from birth until the end of the study, and the surgical intervention was performed under infrared illumination (49). Four eyes were used for quantification of RHO knockdown efficiency at the RNA and protein levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of Mutant RHO with shRNA 820 . To verify the efficiency of shRNA 820 in heterozygous mutant retinas that express both WT and mutant RHO alleles, subretinal injections of AAV-shRNA 820 were performed over a range of titers (1 × 10 11 to 10 × 10 11 vg/mL) in 10 RHO-mutant eyes that were followed for 8-10 wk postinjection (SI Appendix, Table S1 groups D and E) Since the RHO-mutant dog retinas are highly sensitive to light (45)(46)(47)(48), the animals were housed under dim red light from birth until the end of the study, and the surgical intervention was performed under infrared illumination (49). Four eyes were used for quantification of RHO knockdown efficiency at the RNA and protein levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we evaluated whether knockdown alone could arrest photoreceptor degeneration. Another set of four RHO-mutant eyes (SI Appendix, Table S1 group E) were also injected with the same range of titers of AAV-shRNA 820 , but at 6-8 wk postinjection they were exposed for 1 min to moderate-intensity white light known to cause acute retinal degeneration in this canine model (46)(47)(48). Two weeks after light exposure, the eye injected with the titers of 10 × 10 11 and 5 × 10 11 vg/mL showed a distinct region of ONL retention corresponding to the treatment area ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In their recent study, Orlans et al found that retinal degeneration in RhoP23H/+ mice was significantly slower when the mice were housed in red-tinted cages than in untinted cages [2]. Some studies have also shown that retinal damage in rhodopsin-related RP animal models was more sensitive to light and that the progression of retinal degeneration was slower in dark environments [3,4].…”
Section: To the Editormentioning
confidence: 99%
“…A spontaneous dog model of RHO adRP has been identified [18]. The c.11C>G, p.Thr4Arg mutant dog (Rho T4R ) develops a retinal degeneration that is greatly exacerbated by light exposure [19]. The phenotype of this dog model closely resembles that of the human p.Thr4Lys RHO mutation which results in dominant RP [20].…”
Section: Dog Modelmentioning
confidence: 99%